Stability Study of Iriba Brucellosis Full-dose and Reduced-dose Vaccine Produced by Razi Institute in Iran - Hasannia, E. (Archives of Razi Institute, 2015)
Stability study of biological products plays an important role for determination of product changes in maintenance period and ensuring of safety and efficacy of vaccines. In this research, accelerated and long-term stability study performed for six batches of full and reduced-dose cattle Iriba strain brucellosis vaccine that manufactured by Razi vaccine and serum research institute as a new vaccine. After sampling, the vaccines were tested for accelerated stability, after four days storage at 22 0C and tested intervals in three months until 24 months for long-term stability after storage at 2-8 0C. The result indicated all batches of vaccines in accelerated stability met the specification recommended by OIE 2012 and the mean loss of activity for full-dose was 16.68, 18.87 and 17.79 % and for reduced-dose was 38.85, 36.06 and 34.98 %. In long term stability, the quality control tests including colony forming unit, purity, dissociation and physicochemical tests in all samples until 24 months, met the specification recommended by OIE 2012. The full-dose vaccines showed a mean loss of activity of 30.73, 25.53 and 32.45 % and the reduced-dose vaccines showed 63.51, 58.60 and 60.83 %. The mean increasing of moisture content was, 187.85, 214.13 and 160.77 % for full-dose and 142.35, 110.23 and 164.47 % for reduced-dose. So, the results of this research indicated in spite of moisture content increasing in second year, the brucellosis vaccines with this strain are stable at least 24months if the cold chain considered properly but the best expiry date for the vaccine is one year.